2019
DOI: 10.18502/ijrm.v17i9.5096
|View full text |Cite
|
Sign up to set email alerts
|

Niacin improves maturation and cryo-tolerance of bovine in vitro matured oocytes: An experimental study

Abstract: Background: Nicotinic acid (niacin) is a broad-spectrum lipid-modifying agent that has potent antioxidant properties and reduces the production of lipid peroxidation. Objective: The purpose of the present study was to investigate the maturation, embryo development and cryo-tolerance merit, and levels of malondialdehyde (MDA), total oxidant status, and total antioxidant capacity following the supplementation of bovine oocytes maturation medium with different concentrations of niacin. Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Consistent with this, previous studies have also shown an improvement in oocyte quality when mouse follicles cultured in vitro were supplemented with NA [ 29 ]. Bovine oocytes treated with 400 µM NA also exhibited significant improvements in meiotic progression and developmental competence following vitrification [ 30 ], and blastocyst formation was significantly improved when porcine oocytes isolated from large antral follicles were supplemented with 600 µM niacin during IVM [ 31 ]. There was no effect on aged, in vitro matured murine oocytes at low doses of NA [ 18 ], however, a significant increase in intrinsic oocyte NAD + levels in the oocytes from aged mice compared with control mice was observed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, previous studies have also shown an improvement in oocyte quality when mouse follicles cultured in vitro were supplemented with NA [ 29 ]. Bovine oocytes treated with 400 µM NA also exhibited significant improvements in meiotic progression and developmental competence following vitrification [ 30 ], and blastocyst formation was significantly improved when porcine oocytes isolated from large antral follicles were supplemented with 600 µM niacin during IVM [ 31 ]. There was no effect on aged, in vitro matured murine oocytes at low doses of NA [ 18 ], however, a significant increase in intrinsic oocyte NAD + levels in the oocytes from aged mice compared with control mice was observed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, supplementing the maturation media with NA in this study potentially provided the oocyte with a much greater capacity to produce NAD + than was possible from tryptophan alone. Together the findings suggest that the effective concentration of NA for improving oocyte quality differs between species and oocytes from follicles of different diameter [ 18 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maturation medium included of TCM-199 supplemented with 0.1 IU/mL recombinant human FSH (Follitrope, LG Life Sciences, South Korea), 5 IU/mL highly purified hCG (Karma, Pharmatech GmbH, Germany), 50 μg/mL gentamicin, and 10% FCS. This experiment was carried out in five independent replicates (15).…”
Section: Experiments 1: Ivm Of the Bovine Oocytementioning
confidence: 99%
“…On the day of evaluation, 1% aceto-orcein dye (1% orcein in 45% glacial acetic acid) was used to stain the COCc which were mounted on microscopic slides and examined in terms of nuclear morphology with a light microscope at × 100 and × 400 magnifications. Based on their nuclear status, the oocytes were categorized as mature, immature, metaphase І, and abnormal (any spindle and chromosomal abnormality) (15).…”
Section: Assessment Of the Ivmmentioning
confidence: 99%
See 1 more Smart Citation